Compliance with Iron Supplementation Consumption in Pregnant Women on Hematological Profiles and Ret-He - Nugraha, Gilang; Edijanto, Subagijo Poegoeh; Masruroh, Nur (Jurnal Analis Medika Biosains (JAMBS), 2024)
Fetal growth will increase the mass of maternal and fetal erythrocytes resulting in an increase in iron requirements, causing a decrease in maternal iron stores.A decrease in iron in the body will disrupt the formation of hemoglobin, because one of the components that forms it is heme which contains iron. the aim of our research is to study the compliance of pregnant women in consuming iron supplements regarding hematological features and body iron reserves through the Ret-He examination. This research is a cross-sectional study in 30 pregnant women for complete blood count (CBC), Ret-He and estradiol. There were differences in the concentrations of Hgb and MCHC (P-value < 0.05) and there were no differences in the concentrations of Hct, RBC, MCV, MCH, RDW, Ret-He and estradiol (P-value > 0.05). It was found that there was a relationship between estradiol and Hgb (P-value = 0.047; r = 0.366). Pregnant women who do not comply with taking iron supplements experience a decrease in Hgb and MCHC. The decrease in Hgb levels is strongly correlated with E2 levels in pregnant women who adhere and do not comply with iron supplementation.